The distribution of Coleoptera Wrechers on agricultural cultures, their trofical communications with plants of natural lanshafts - H. U. Dudarova; Sh. G. Abdurahmanov (Юг России: экология, развитие)
For the first time in the article the data about Coleoptera insects, harming agricultural crops in Ingushetia Republic, their distribution on agricultural crops, trophic communications with vegetation of natural landscapes are cited.